Host–Guest Complexation Using Pillar[5]arene Crystals: Crystal‐Structure Dependent Uptake, Release, and Molecular Dynamics of an Alkane Guest. Issue 10 (25th January 2019) - Ogoshi, Tomoki; Hamada, Yukie; Sueto, Ryuta; Sakata, Yoko; Akine, Shigehisa; Moeljadi, Adhitya Mangala Putra; Hirao, Hajime; Kakuta, Takahiro; Yamagishi, Tada‐aki; Mizuno, Motohiro
Abstract: Host–guest complexation has been mainly investigated in solution, and it is unclear how guest molecules access the assembled structures of host and dynamics of guest molecules in the crystal state. In this study, we studied the uptake, release, and molecular dynamics of n ‐hexane vapor in the crystal state of pillar[5]arenes bearing different substituents. Pillar[5]arene bearing 10 ethyl groups yielded a crystal structure of herringbone‐type 1:1 complexes with n ‐hexane, whereas pillar[5]arene with 10 allyl groups formed 1:1 complexes featuring a one‐dimensional (1D) channel structure. For pillar[5]arene bearing 10 benzyl groups, one molecule of n ‐hexane was located in the cavity of pillar[5]arene, and another n ‐hexane molecule was located outside of the cavity between two pillar[5]arenes. The substituent‐dependent differences in molecular arrangement influenced the uptake, release, and molecular dynamics of the n ‐hexane guest. The substituent effects were not observed in host–guest chemistry in solution, and these features are unique for the crystal state host–guest chemistry of pillar[5]arenes. Abstract : Gasses in crystals : The uptake, release, and molecular dynamics of n ‐hexane vapor in the crystal state of pillar[5]arenes bearing different substituents was studied (see figure). The substituent‐dependent differences in molecular arrangement influenced the uptake, release, and molecular dynamics of the n ‐hexane guest.